2021
DOI: 10.3389/fphar.2021.790321
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Studies of Chinese Herbal Medicine: Pleiotropic Role of DNA Methylation

Abstract: Accumulating knowledge has been achieved on DNA methylation participating in numerous cellular processes and multiple human diseases; however, few studies have addressed the pleiotropic role of DNA methylation in Chinese herbal medicine (CHM). CHM has been used worldwide for the prevention and treatment of multiple diseases. Newly developed epigenetic techniques have brought great opportunities for the development of CHM. In this review, we summarize the DNA methylation studies and portray the pleiotropic role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 92 publications
(104 reference statements)
0
4
0
Order By: Relevance
“…Recent studies have found that the occurrence and development of inflammation are accompanied by abnormal changes in DNA methylation [1,2]. DNA methylation is the most common epigenetic modification and is mediated by DNA methyltransferases (DNMTs, including DNMT3a and DNMT3b) [3].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found that the occurrence and development of inflammation are accompanied by abnormal changes in DNA methylation [1,2]. DNA methylation is the most common epigenetic modification and is mediated by DNA methyltransferases (DNMTs, including DNMT3a and DNMT3b) [3].…”
Section: Introductionmentioning
confidence: 99%
“…Chromatin accessibility is crucial for maintaining precise regulation of gene expression (Buenrostro et al, 2013;Buenrostro et al, 2015;Guo et al, 2021;Chen, G et al, 2023). The regulatory elements controlling gene expression can be broadly categorized into three types: promoters, enhancers, and boundary elements (such as insulators and boundary enhancer), among which, promoters are primarily located at the TSS while enhancers and boundary elements are often situated at distal positions away from genes (Oudelaar & Higgs, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetics are changes in gene expression without changes in DNA sequences and plays a role in cellular processes in various diseases (Ling and Ronn, 2019;Guo et al, 2021). Epigenetic changes can be caused by at least three mechanisms including DNA methylation, post-translational histone modifications, and regulation of gene expression by non-coding RNA (ncRNA) which can be microRNA (miRNA), long non-coding RNA (lncRNA), etc (Xiao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%